Membangun Niat Beli Melalui Pengalaman dan Kualitas Layanan: Studi pada Konsumen Sport Fotografi “The Angle Sport” - Mubarok, Dimas Hamdan; Nahdi, Moehammad Robith (CV. Lentera Literasi Indonesia, 2025)
This study aims to determine the role of experiential marketing and service quality on purchase intentions through customer satisfaction as an intervening variable for users of The Angle Sport photographer services. The quantitative explanatory method is the research method used in this research by searching for data using a survey, namely distributing questionnaires to a predetermined sample of 170 respondents. The respondents of this research are football or futsal fans in Malangraya who have used the services of sports photographer The Angle Sport. The data analysis method uses the Partial Least Aquare approach assisted by the SmartPLS application. From the research results it can be concluded that there is a significant positive influence between service quality on customer satisfaction, service quality on repurchase intention, customer satisfaction with repurchase intention and service quality has a significant positive influence on repurchase intention through customer satisfaction. However, there is an insignificant positive influence between experiential marketing on customer satisfaction, experiential marketing on repurchase Intention, and experiential marketing on repurchase decisions through customer satisfaction.